Enhancing oncolytic virotherapy by extracellular vesicle mediated microRNA reprogramming of the tumour microenvironment - Jennings, Victoria A.; Rumbold-Hall, Reah; Migneco, Gemma; Barr, Tyler; Reilly, Katrina; Ingram, Nicola; St Hilare, Isabelle; Heaton, Samuel; Alzamel, Noura; Jackson, David; Ralph, Christy; Banerjee, Susan; et al. (Frontiers in Immunology, 2024)
BackgroundThere has been limited success of cancer immunotherapies in the treatment of ovarian cancer (OvCa) to date, largely due to the immunosuppressive tumour microenvironment (TME). Tumour-associated macrophages (TAMs) are a major component of both the primary tumour and malignant ascites, promoting tumour growth, angiogenesis, metastasis, chemotherapy resistance and immunosuppression. Differential microRNA (miRNA) profiles have been implicated in the plasticity of TAMs. Therefore, delivering miRNA to TAMs to promote an anti-tumour phenotype is a novel approach to reverse their pro-tumour activity and enhance the efficacy of cancer immunotherapies. Oncolytic viruses (OVs) preferentially replicate in tumour cells making them ideal vehicles to deliver miRNA mimetics to the TME. Importantly, miRNA expressed by OVs get packaged within tumour-derived extracellular vesicles (TDEVs), and release of TDEV is augmented by OV infection, thus enhancing the dissemination of miRNA throughout the TME.MethodSmall RNA sequencing was used to identify differentially expressed miRNA during TAM generation and following LPS/IFNγ stimulation to induce an anti-tumour phenotype. Two differentially expressed miRNA identified, miR-155 and miR-19a, were cloned into oncolytic rhabdovirus (ORV), and anti-tumour efficacy was investigated using both in vitro and in vivo models of OvCa.ResultsThis study demonstrates that ORV infection enhances TDEV production in OvCa cell lines both in vitro and in vivo and that TDEV are preferentially taken up by myeloid cells, including TAMs. Small RNA sequencing identified 23 miRNAs that were significantly upregulated in anti-tumour TAMs, including miR-155-5p. While 101 miRNAs were downregulated during pro-tumour TAM differentiation, including miR-19a-3p. Culturing TDEV expressing miR-155 or miR-19a with TAMs reversed their immunosuppressive activity, as measured by T cell proliferation. While ORV-miR-155 enhanced the generation of anti-tumour T cells, only ORV-miR19a significantly improved survival of mice bearing ovarian tumours.ConclusionThis study demonstrates (i) that arming ORVs with immunomodulatory miRNA is an effective approach to deliver miRNA to myeloid cells within the TME and (ii) that miRNA have the capacity to reverse the tumour promoting properties of TAMs and improve the efficacy of cancer immunotherapies, such as OV.